La race ovine Djallonke au Cameroun. Potentialites zootechniques, conditions d'elevage, avenir - Vallerand, F.; Branckaert, R. (1975)
Studies the breed characteristics of Djallonke sheep in Cameroon. Discussions on morphology, reproduction, selection and socio-economic evaluation details given. Performance in terms of prolificacy, fecundity, birth weight, milk yield as measured by lamb daily gain and mortality included. Recommendations on future ovine rearing targeted at marketing, animal disease and disease control included.